Strategi Pemasaran Pada Kedai Kopi Sanggabuana Di Desa Mekarbuana Kecamatan Tegalwaru Kabupaten Karawang - Nur Itihadah; Abubakar Abubakar; Luthfi Nur’azkiya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Coffee is a plantation commodity which is categorized as a strategic commodity in Indonesia. Coffee consumption is now a complement to community activities, so the amount of coffee consumption will continue to increase. The Sanggabuana Coffee Shop is a coffee shop business that is experiencing problems in its marketing. The purpose of this study is to analyze marketing strategies and determine priority strategies at the Sanggabuana Coffee Shop, Karawang Regency. The time of this research was carried out from February to March 2022. The location of the research was at the Sanggabuana Coffee Shop, Mekarbuana Village, Tegalwaru District, Karawang Regency. The choice of research location was done purposively. The research method used is descriptive with qualitative and quantitative approaches. This study uses primary data and secondary data. Primary data collection using interview techniques using questionnaires, the respondents of this study consisted of key informants (Head of the Sanggabuana Coffee Shop, Head of BUMDes Buana Mekar, Head of Mekar Buana Village) and non-key informants (consumers 3 people). Secondary data were obtained from the Central Statistics Agency and the Mekarbuana Village Government. The sample was determined by purposive sampling. The data analysis of this research used SWOT and QSPM analysis. The results of the study based on the SWOT analysis obtained 7 alternative strategies, and then a QSPM analysis was carried out so that the main strategic priority with the highest STAS value of 6.60 was establishing marketing cooperation with the government.